Cross-cultural adaptation of Rotter's General Locus of Control instrument - Calado,Gabriel de Almeida (2018)
Abstract Objective To perform a cross-cultural adaptation of the General Locus of Control (GLoC) questionnaire, which measures where people place causation of events in their lives, i.e., if they interpret events as being the result of their own actions or external factors. Methods After translation and back-translation, a multidisciplinary committee judged and elaborated different versions of the GLoC questionnaire, with a focus on conceptual equivalence, content, comprehensibility and adjustment to the Brazilian socioeconomic context. The final version was tested on 71 healthy subjects, of whom 36 were reinterviewed and answered the GLoC questionnaire twice, after a mean of 73.06±74.15 days (range = 29-359). Results The participants' mean age was 30.82±12.83 years (range = 18-69), 62% were women, and mean years of schooling were 12.54±4.21. Test-retest reliability (Pearson's) was r = 0.828. Internal consistency resulted in a Cronbach's alpha of 0.906. The mean GLoC score obtained was 8.77±3.11 (n = 71). Conclusion The Portuguese version of the GLoC questionnaire is a faithful adaptation of Rotter's original questionnaire.